Position management on pulmonary function and bronchopulmonary dysplasia in premature infants: study protocol for a randomised controlled trial - Liu Yang; Zhengrong Bao; Lianyu Zhang; Xiaoping Lei; Lingping Zhang (BMJ Open)
Introduction Bronchopulmonary dysplasia (BPD) is a common disease caused by various factors and mechanisms in premature infants. Owing to lung hypoplasia and the lack of alveolar surfactants in premature infants, oxygen therapy is often needed to maintain adequate breathing. Nevertheless, prolonged oxygen therapy can easily induce BPD, and there is currently no effective treatment. Therefore, the prevention of BPD in premature infants during hospitalisation is essential. Studies have revealed that the prone position can effectively improve the oxygenation of premature infants. However, a few studies have reported whether prone positioning can improve lung function and reduce BPD incidence. This trial will determine whether the prone position, compared with the supine position, can reduce BPD incidence and improve lung function in preterm infants.Methods and analysis This study protocol is for a single-centre, single-blind, randomised controlled trial of the prone position in premature infants. Following daily feeding, premature infants will be placed in the lateral position for 30 min; then they will be turned to the supine position (control group) or prone position (intervention group) for 2 hours each in the morning and afternoon. Moreover, infants in both groups will be placed in the supine or lateral position alternately according to their medical needs for the remaining time. The study begins when the premature infants are stable within 5 days after admission and ends when they are discharged from the hospital or at 36 weeks postmenstrual age. The primary outcome is the survival rate without BPD. The secondary outcomes include lung function parameters and lung oxygen saturation.Ethics and dissemination This trial is approved by the ethics committee of the Affiliated Hospital of Southwest Medical University, (ref approval no.KY2021186). The results will be published in a peer-reviewed journal.Trial registration number ChiCTR2100049847.